ANALISIS SOSIOLEK BAHASA PADA KOMUNITAS ROBLOX: RAGAM SLANG SEBAGAI KONSTRUKSI IDENTITAS DIGITAL - Dewi Anggraini; Falina Noor Amalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research examines the use of slang in the Roblox community as part of digital identity construction and sociolect practices within online communication spaces. The phenomenon emerges through virtual interactions that develop a distinctive linguistic pattern, where non-standard expressions function as indicators of membership, social hierarchy, and cultural affiliation among players. A descriptive qualitative approach was applied using documentation of conversations, non-participatory observation, and screenshots collected from the Discord server “YAHAYUK Community.” Data were analyzed based on meaning, social functions, and usage context, supported by source and methodological triangulation to ensure validity. Findings reveal 25 recurring slang terms, including carry, bacon, robux, push, summit, and AFK, functioning to support communication efficiency, gameplay coordination, status markers, digital economic identity, and group solidarity. These linguistic forms are both pragmatic and symbolic, reinforcing norms, shared knowledge, and interpersonal relations within the gaming community. Thus, slang usage in the Roblox environment forms a digital sociolect that represents group identity, social structure, and a distinctive communication culture in virtual spaces. Language transcends its instrumental role and becomes a medium for identity formation, social bonding, and cultural practice within online game communities.